Segmentasi Pelanggan Penjualan Online Menggunakan Metode K-means Clustering - Ardana, Candra Hafidz; Khoyum, Adlian Aldita Alif Aisyah Ainur; Faisal, Muhammad (UIN Sunan Kalijaga Yogyakarta, 2024)
Customer segmentation is an essential strategy in the online selling industry to understand customer preferences and behavior. This article proposes applying the K-means clustering method in online sales customer segmentation. The method used is the descriptive method. The steps of the research method include literature studies and data processing to be analyzed using the K-means clustering method. The K-means clustering method is then applied to customer data to group it based on relevant attributes. The segmentation results are evaluated and scored using the clustering evaluation metric. The main objective is to explain the use of the K-means clustering method in online sales customer segmentation, focusing on obtaining more profound insights into customer behavior. Efficient customer segmentation allows companies to target customer groups more precisely and efficiently. This article provides practical insights and guidance for e-commerce companies in implementing customer segmentation using K-means clustering to increase efficiency in targeting segmented customers.